MICROBIAL COMMUNITY PROFILING OF DIGESTED SLUDGE FROM PILOT PLANT BIO-DIGESTER - ISMAIL, ISMAFATIN NABILAH; ISMAIL, SHAHRUL; MOHAMED ZAHARI, MOHAMED SHAHRIR (Universiti Malaysia Terengganu Journal of Undergraduate Research, 2021)
The production of biogas involves different microbial groups working in a synchronously and closely interactive manner. In Malaysia, biogas production from food waste is an encouraging alternative for sustainable energy production. Therefore, to better understand and optimize process, identification of the microbial community involved in anaerobic digestion (AD) is essential. The purpose of this study is to identify the microbial characteristics under different AD conditions to establish the links between microbial community structure and operational condition efficiency. The pilot plant bio-digester production performance will be determined by analysis of Chemical Oxygen Demand (COD) removal efficiency for 43 days. Next, when the performance of the digester has achieved an optimum level of removal efficiency, a sample of digested sludge will be taken for further analysis of microbial community profiling by undergo DNA extraction, amplifying DNA and Next Gene Sequencing (NGS) technology. The results show that the COD removal efficiency at an optimum level is 93%, while the percentage of methane gas composition inside the digester is 69%, indicating a very high efficiency for the digester. Thus, the lower the concentration of COD effluent, the higher the concentration of COD removal efficiency. Besides, an optimum an optimum level of COD removal efficiency indicates active microbial activities inside the bio-digester. Furthermore, the microbial community structure with operational conditions at various states of anaerobic digestion is summarizing. These findings are important as microbial characteristics of digested sludge is important to manage and optimize biogas production.